Mendorong Kreativitas dan Pemahaman Makna melalui Pembelajaran Mendalam dalam Pengajaran Menulis Bahasa Indonesia - Anita Candra Dewi; Sakinah Fitri; Irma Satriani; Rizki Herdiani (Journal of Humanities, Social Sciences, and Education, 2025)
In 21st-century education, writing skills in Indonesian language learning are no longer simply defined as the ability to construct words and sentences, but rather as a higher-order thinking process involving analysis, reflection, and in-depth interpretation of experiences and social contexts. The integration of a deep learning approach into writing instruction offers a new paradigm oriented toward students' understanding of meaning, creativity, and critical thinking skills. Through this literature review, researchers analyzed various recent research findings on the application of deep learning in the context of teaching Indonesian language writing in schools. The results of the review indicate that deep learning strategies can encourage students to understand the structure and meaning of texts more reflectively, develop original ideas, and build connections between personal experiences and socio-cultural contexts. Furthermore, teachers play a crucial role in creating a collaborative learning environment that stimulates students' critical thinking and creative expression. Deep learning-based writing instruction has also been shown to strengthen higher-order thinking skills and shift the learning paradigm from mere knowledge reproduction to meaning construction.